Mathematics in 'the news': number theory and number sense. Issue 567 (November 2022) - Rowland, Tim
Abstract : Time spent in national pandemic 'lockdowns' and 'tiers' for most of 2020 has created an opportunity to revisit some ideas previously committed to paper, but unfinished. I now return to one of them, to continue and share the line of thought, if not to complete it.